Kajian Strukturalisme Todorov dalam Cerpen Berciri Realisme Magis: Todorov’s Structuralism in a Short Story with Magical Realism - Ismail Marzuki; Ahmad Rifa'i; Karoluslina Karoluslina (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to reveal the representation of Tzvetan Todorov’s structuralism in the short story Memanggil Roh Singa (“Summoning the Lion’s Spirit”), which contains elements of magical realism. Todorov’s structuralist approach is employed to examine the relationship among the intrinsic elements, particularly the narrative facts, theme, and literary devices. The short story is analyzed using a qualitative descriptive method through close reading of the text and identification of its narrative structure based on Todorov’s framework, as well as an analysis of the characteristics of magical realism using Wendy B. Faris’s theory to validate its magical aspects. The results indicate that Memanggil Roh Singa represents Todorov’s distinctive structural pattern, consisting of 21 narrative sequences dominated by flashbacks. The setting portrays magical elements with a ritual theme of “kammala”, narrated from a first-person point of view. The narration is dominated by metaphorical and personifying language, enriched with mystical symbols. This research demonstrates that Todorov’s structuralism is effective in uncovering the layers of meaning within a short story characterized by magical realism, as it reveals the coherence between the narrative structure and its embedded mystical dimensions.